Exploring The Challenges Of Implementing International Financial Reporting Standards (IFRS) - Muhammad Rizal; Eri Kusnanto (Universitas Veteran Bangun Nusantara, 2021)
This study aims to identify the challenges and factors influencing the successful implementation of International Financial Reporting Standards (IFRS) in Indonesia. Utilizing a qualitative approach, data were gathered through in-depth interviews with regulators, auditors, and financial executives. The findings reveal that the lack of institutional infrastructure, the complexity of IFRS standards, and cultural and linguistic differences are significant barriers to IFRS adoption in Indonesia. Despite these challenges, potential benefits such as enhanced transparency and comparability are recognized, with capacity-building initiatives needed for successful implementation.